KAJIAN HUBUNGAN HARA TANAH TERHADAP PRODUKTIVITAS TANAMAN TEH PRODUKTIF DI PERKEBUNAN TEH PAGAR ALAM, SUMATERA SELATAN - Azurianti Azurianti; Restu Wulansari; Faris Nur Fauzi Athallah; Sugeng Prijono (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2022)
Tea plantation area in recent years has decreased by 0.75% annually. With the decline in the area of tea plantations, productivity also decreases. Decreased productivity can be caused by erosion, climate, clones, and management applications. The purpose of this study was to determine the availability of soil nutrients in Pagar Alam tea plantation and the relationship with productivity. The observation was held with secondary data and analyzed statistically with the correlation method. Parameters observed were pH, organic C, total N, P2O5, exchangeable K, and exchangeable Mg. The result showed that the relationship between soil nutrients such as organic C, total N, available P, exchangeable K, and exchangeable Mg with productivity was weak with correlation coefficient values of 0.00 – 0.199. These results also showed that the correlation was negative, which means that the two variables were inversely proportional. Plant maintenance factors have a more significant role in tea plant productivity than nutrients and fertilization, such as picking, pruning, root zone improvement, and plant pest control. If these factors can be controlled properly, shoot production will increase, and plant health can be maintained. Thus, in this case, the nutrient factor is not the main factor affecting productivity at Pagar Alam Tea Plantation, indeed the plant care factor.